Abnormal cortical synaptic transmission in CaV2.1 knockin mice with the S218L missense mutation which causes a severe familial hemiplegic migraine syndrome in humans - Vecchia, Dania; Tottene, Angelita; van den Maagdenberg, Arn M.J.M.; Pietrobon, Daniela (Frontiers in Cellular Neuroscience, 2015)
Familial hemiplegic migraine type 1 (FHM1) is caused by gain-of-function mutations in CaV2.1 (P/Q-type) Ca2+ channels. Knockin (KI) mice carrying the FHM1 R192Q missense mutation show enhanced cortical excitatory synaptic transmission at pyramidal cell synapses but unaltered cortical inhibitory neurotransmission at fast-spiking interneuron synapses. Enhanced cortical glutamate release was shown to cause the facilitation of cortical spreading depression (CSD) in R192Q KI mice. It, however, remains unknown how other FHM1 mutations affect cortical synaptic transmission. Here, we studied neurotransmission in cortical neurons in microculture from KI mice carrying the S218L mutation, which causes a severe FHM syndrome in humans and an allele-dosage dependent facilitation of experimental CSD in KI mice, which is larger than that caused by the R192Q mutation. We show gain-of-function of excitatory neurotransmission, due to increased action-potential evoked Ca2+ influx and increased probability of glutamate release at pyramidal cell synapses, but unaltered inhibitory neurotransmission at multipolar interneuron synapses in S218L KI mice. In contrast with the larger gain-of-function of neuronal CaV2.1 current in homozygous than heterozygous S218L KI mice, the gain-of-function of evoked glutamate release, the paired-pulse ratio and the Ca2+ dependence of the EPSC were all similar in homozygous and heterozygous S218L KI mice, suggesting compensatory changes in the homozygous mice. Furthermore, we reveal a unique feature of S218L KI cortical synapses which is the presence of a fraction of mutant CaV2.1 channels being open at resting potential. Our data suggest that, while the gain-of-function of evoked glutamate release may explain the facilitation of CSD in heterozygous S218L KI mice, the further facilitation of CSD in homozygous S218L KI mice is due to other CaV2.1-dependent mechanisms, that likely include Ca2+ influx at voltages sub-threshold for action potential generation.